The Relationship Between Knowledge, Motivation, and Supervision Towards Documentation Among Nurses at Private Hospital in Indonesia - Suryani, Lilis; Masmulyadi, Masmulyadi; Perdani, Agni Laili (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Nursing care documentation is an essential part and integrated within the nursing process. The previous study described incomplete nursing records, reflecting the quality of nursing care and implementation of patient safety. This study aim is to explore the relationship between knowledge, motivation and supervision toward nursing documentation. Method: A descriptive-quantitative research method with a cross-sectional approach was implemented. A total of 64 respondents are agreed to participate with the convenience sampling method in one month in December 2020. Data collection used a self-report questionnaire and observational form with the accepted value of validity and reliability. Data analysis by bivariate with Chi-square and multivariate with Logistic. Results: Nurses showed good knowledge (n=57; 89.1%) and motivation (n=35;54.7 %) whilst poor supervision (n=31;48.4) and documentation (n= 40; 62.5%) Supervision is statistically significant had relationship with nursing documentation OR 3.333 (1.151-9.650) p-value < 0.05 and strong associated with nursing documentation β = 3.517 (1.182-10.469). Conclusion: Increasing knowledge, motivation, supervision is needed to protect both nurses and patients. Supervision activities are the tools to evaluate the nursing process and ensure continuity of care.